Association Between Parenting Style and Social Outcomes in Children with and Without Attention-Deficit/Hyperactivity Disorder: An 18-Month Longitudinal Study. Issue 6 (July 2017) - Bhide, Sampada; Sciberras, Emma; Anderson, Vicki; Hazell, Philip; Nicholson, Jan M.
ABSTRACT: Objective: In a community-based sample of children with attention-deficit/hyperactivity disorder (ADHD) (n = 179) and non-ADHD controls (n = 212), this longitudinal study explored changes in parenting style over time; and whether parenting style prospectively predicts child functional outcomes. Methods: Attention-deficit/hyperactivity disorder diagnosis was assessed using the Conners ADHD index and Diagnostic Interview Schedule for Children IV. Children (70.3% boys) were assessed at baseline (mean age: 7.3 yr) and after 18 months (mean age: 8.9 yr) using a range of parent- and teacher-reported measures of child socioemotional and academic functioning. Parenting style was assessed through parent-reported measures of warmth, consistency, and anger. Results: At 18-month follow-up, there was a small significant decline in parenting warmth and parenting anger, and an increase in parenting consistency across groups. In the ADHD group, parenting warmth at baseline was positively related to 18-month prosocial behavior and responsibility by parent report, whereas parenting consistency predicted these child outcomes by teacher report. Parenting anger was positively associated with peer problems and negatively associated with prosocial behavior, self-control, and responsibility by parent report. Associations were similar for non-ADHD controls and all associations held after adjusting for a range of family, child, and parent factors. After additional adjustment of baseline levels of child functioning, parenting warmth and consistency continued to be associated with 18-month child outcomes. Parenting style was unrelated to emotional problems and academic competence over time. Conclusion: Parenting style is independently related to aspects of future social outcomes of children with ADHD. Results hold implications for parenting interventions aimed at managing ADHD-related social impairments over time. Abstract : This article has supplementary material on the web site: www.jdbp.org.